Leukemia and Myeloproliferative Disorders Summarized - Cunningham, Muriel (MD Conference Express, 2014)
This article provides an overview of leukemia and myeloproliferative diseases in veterinary medicine. The clinical signs of leukemia can be vague and include lethargy, change in behavior, weight loss, petechiation, cytopenias, and enlarged peripheral lymph nodes or spleen. Often, these cases are detected incidentally, particularly with chronic lymphocytic leukemias.